Karyological analysis for endangered fish, Hucho taimen (Pallas) - QUN, XUE SHU; WEN, SUN XIAO; SHENG, YIN JIA (The Indian Journal of Animal Sciences, 2012)
Metaphase chromosome specimens of Hucho taimen injected with PHA and colchicin, were prepared from short- term culture of kidney cells with air-drying technique. Its diploid chromosome number is 2n = 84. The karyotype formula proposed for Hucho taimen was 2n =18m+16sm+34st+16t, and the arm number was NF=118.